Backlash or a Positive Response?: Public Opinion of LGB Issues After Obergefell v. Hodges. Issue 14 (6th December 2018) - Kazyak, Emily; Stange, Mathew
ABSTRACT: Following Obergefell v. Hodges, same-sex marriage remains controversial and anti-LGBT state legislation has been passed, which raises questions about whether the Supreme Court's ruling may have created a backlash. We use data from two waves of a general population survey of Nebraskans conducted before and after the decision to answer three questions. First, we test three theories of how the court decision influenced public opinion. We find that support for same-sex marriage was significantly higher following the ruling, suggesting that there was not a backlash to it. Second, we assess whether people perceive that the court accurately reflects the public's opinion. We find that people who favor same-sex marriage are more likely to think that the ruling refects public opinion very well; those who oppose same-sex marriage are more likely to think that the ruling does not at all reflect public opinion. Third, we examine the association between discussing gay rights and support for same-sex marriage, finding that those who talk about LGB issues very often are more likely to favor same-sex marriage. We discuss the implications of these findings in relation to two of the themes of this special issue: the influence of marriage equality on Americans' understandings of marriage and the impact of marriage equality on future LGBT activism.